Association between C-reactive protein levels and physical fitness in 7 to 9 year old children at poor elementary schools in Surakarta, Indonesia - Lilisianawati Lilisianawati; Endang Dewi Lestari; Diana Mayasari Hadianto; Maria Galuh Kamenyangan Sari; Leilani Lestarina; Harsono Salimo (Indonesian Pediatric Society, 2009)
Background Data regarding inflammatory factors in children arenot so well developed as in adults. Higher levels of physical fitnessmay be helpful in modifying the low-grade inflammatory state thatis indexed by C-reactive protein (CRP) levels.Objective To evaluate the association of physical fitness with CRPlevels in children and to identify the possible related factors.Methods This cross-sectional study was conducted at poorelementary schools in Surakarta, Indonesia using a group of 217underweight children aged from 7 to 9 years old. Physical fitnesswas assessed using a modified Harvard Step Test. CRP levels weremeasured using a high-sensitivity assay. The association betweenphysical fitness and CRP level was assessed using linear regressionanalysis. Multivariate analyses were used to adjust covariates,and statistical analyses were performed using SPSS for Windowssoftware version 15.0.Results Subjects were 48% female and 52% male, and elevenchildren (5%) had a CRP level > 5 mg/L. Mean fitness level andCRP level did not differ by age and gender. Fitness level was notinversely correlated with CRP (r=0.10, P=0.14). Physical fitnesswas significantly correlated with BMI (r=0.14; P=0.04), physicalactivity [0R=3.3 (95% CI 1.7 to 6.4)], and fat intake [0R=0.5(95% CI 0.2 to 0.9) ].Conclusion These findings indicate that physical fitness is notinversely correlated to CRP levels in children. However, ourstudy reveased an association between high fat intake and lowphysical fitness as well as a significant association betweenhigh physical activiry and physical fitness.